The correlates of conflict and behavioural difficulties on the negative affect in at-risk youth in Malaysia - Nor Ba’yah Abdul Kadir,; Suzana Mohd. Hoesni,; Siti Marziah Zakaria,; Hilwa Abdullah@Mohd. Nor,; Noordeyana Tambi,; Mimi Hanida Abdul Mutalib, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Parent-youth conflict and behavioural difficulties are common issues in the field of developmental psychology. This study examines the correlations of conflict and behavioural difficulties, to see if these factors predicted a negative affect on a sample of at-risk youth. A sample of 335 at-risk youth aged 13-24 years old from Public Housing Projects in Kuala Lumpur was selected. Conflict with the father was significantly associated with negative affect. Further analysis showed that three factors were re-quired to produce negative affect. The results support claims that father conflict, emotional problems and conduct problems are an integral part of the close relationships of at-risk youth, and discourage positive youth development among at-risk youth.